2021
DOI: 10.3390/molecules26144325
|View full text |Cite
|
Sign up to set email alerts
|

Fluorimetric Analysis of Five Amino Acids in Chocolate: Development and Validation

Abstract: Amino acids present ergogenic action, helping to increase, protect, and restore the muscular system of young athletes. Moreover, the encapsulation of five relevant amino acids in chocolate pellet form will appeal to them, facilitating their daily consumption. A reliable HPLC fluorimetric method was developed to detect and quantitatively determine L-Leucine, L-Isoleucine, L-Histidine, L-Valine, and β-Alanine in chocolate using aniline as an internal standard. Experimental design methodology was used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In conclusion, a pre‐column derivatization is a crucial tool for analyzing BCAAs due to its ability to enhance detection sensitivity and its versatility in accommodating various sample types and detectors. Table 1 shows a compilation of 19 commonly used derivatization reagents, along with a summary of their respective advantages and disadvantages [33–55]. The different reactions with AAs are described in Figure 2.…”
Section: Derivatization Approachesmentioning
confidence: 99%
“…In conclusion, a pre‐column derivatization is a crucial tool for analyzing BCAAs due to its ability to enhance detection sensitivity and its versatility in accommodating various sample types and detectors. Table 1 shows a compilation of 19 commonly used derivatization reagents, along with a summary of their respective advantages and disadvantages [33–55]. The different reactions with AAs are described in Figure 2.…”
Section: Derivatization Approachesmentioning
confidence: 99%
“…Under these conditions, one of the most important factor to be studied was pH (Table 2) in the range of 8.5-11.0. A value of 9 was chosen as Regarding the selection of the appropriate buffer, the use of a borate solution is recommended since, due to its high buffering capacity (pH 8.0-10.0), it prevents the ionization of secondary amino groups [21]. Under these conditions, one of the most important factor to be studied was pH (Table 2) in the range of 8.5-11.0.…”
Section: Figure 2 Stability Study Of Homotaurine and Histidine Deriva...mentioning
confidence: 99%
“…A value of 9 was chosen as optimal since derivatization was assured and the chromatogram was improved (lower tailing factor). Then, the time required for the reaction was also critical [21] and was investigated between 0 and 30 min (Table 3). Based on the results, it was observed that the derivatization is completed immediately, and up to about 30 min, the HOM derivative is relatively stable.…”
Section: Figure 2 Stability Study Of Homotaurine and Histidine Deriva...mentioning
confidence: 99%
See 1 more Smart Citation